KINERJA SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEDAGANG KAKI LI DI KOTA PEKANBARU - Imam Rezki Kurniadi; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to analyze the performance of Civil Service Police Unit (Satpol PP) in the control of street vendors in the city of Pekanbaru and to analyze the factors that hinder the performance of the Civil Service Police Unit under the control of street vendors in the city of Pekanbaru. The method used in this study is a qualitative research method. Sources of data taken from several people related to the research include: municipal police officer, Head of the Control of Civil Service Police Unit, street vendors and Society. Data collection techniques using the technique of interview, observation, and documentation while the data analysis techniques used in this research is qualitative descriptive analysis.Based on the survey results revealed that the implementation of performance Civil Service Police Unit in controlling street vendors in the city of Pekanbaru is still not optimal, it can be seen from the productivity achieved, the responsiveness of officers in the field to the solutions given to street vendors, as well as accountability or responsibility to solve the problem of street vendors Pekanbaru. While the factors that hinder the performance of the Civil Service Police Unit in Control of street vendors in the city of Pekanbaru, namely: 1. HR competency factors, is expected to the municipal police to increase the number of Civil Service Police Unit personnel in anticipation of the violations committed by violators of order and the quality is still very less so, 2. Factors limitations of infrastructure, the availability of infrastructure and budgetary Civil Service Police Unit were not enough and still very inadequate to carry out enforcement activities continuously and consistently, 3. Factors attendant attitude, the attitude of the civil service police unit officers yet can make the public can receive the information submitted. Ability to convey an appeal that is still lacking. The attitude of the officers also were still not mastered how to be a good way to the street vendors.Keywords: Performance Civil Service Police Unit